Influence of Chromophore Concentration and Network Structure on the Photoorientation Properties of Crosslinked - Fernández, R (2009)
An azo prepolymer (TAZ) was synthesized by reaction between Disperse Orange-3 (DO3) and diglycidyl ether of bisphenol A (DGEBA). Selected amounts of TAZ were blended with DGEBA and cured with an aliphatic diamine, either meta-xilylenediamine (MXDA) or polyetheramines (Jeffamine D series). The photoinduced anisotropy and optical storage properties in two series of crosslinked epoxy-based azo polymers with different architectures and chromophore contents (from 3 to 24 in weight) have been investigated. Measurements of the birefringence (Δn) induced with linearly polarized 488 nm light show that the Δn values increases with DO3 weight fraction. Networks with the same chromophore concentration but different backbones exhibit similar levels of induced anisotropy under the same irradiation conditions. The remaining birefringence and relaxation times are influenced by the molecular weight between crosslinks equation image of networks. Higher equation image is reflected in shorter relaxation times and lower remaining birefringence. In terms of the level of induced dichroism measured on relaxed films, it was found an agreement with the remaining anisotropy.